Batang West Side - Diaz, Lav
A Filipino teenager is shot to death on the sidewalk of New Jersey, USA. An investigation starts into his death. His family members and friends are interviewed. Along the way, we find out not only more about him but about the community of Filipinos in America in general, including the destructive effect of the drug "shabu" on its youth. The detective who handles the case also has his own personal demons to settle with his violent past.--amirmu